The particularities of foreign policy’s implementation and EU leading states positions’ coordination - Oksana Mitrofanova (Європейські історичні студії, 2018)
The article touches upon to investigation of the particularities of foreign policy’s implementation and the EU leading states positions’ coordination. The position of leading states politicians towards strengthening of EU security and defense sphere cooperation has been studied. The factor of Permanent structure cooperation (PESCO) creation and the rationale for its expediency has been underlined. The article deals with migration crisis in the EU, the reaction of the European politicians to this issue and the consequences that manifested in the elections to the Italian parliament. The reforms having support of the leaders of France, Germany and Italy have been analyzed.